Excellence in internal communication management - Men, Rita Linjuan; Bowen, Shannon A. (New York Business expert press, 2016)
This book integrates theories, research insights, practices, as well as current issues and cases into a comprehensive guide for internal communication managers and organizational leaders on how to communicate effectively with internal stakeholders, build beneficial relationships, build ethical organizational cultures, and engage employees in a rapidly-changing business and media environment. Solidly grounded in theories of organizational communication and behavior, public relations, leadership, moral philosophy, and business management, this book shares insights about current workplace topics including employee engagement, trust, change communication, new technologies, leadership communication, ethical advising and decision making, transparency and authenticity, and measurement. Mechanisms underlying best practices of internal communication are explained. Data-backed strategies and tactics in enhancing internal communications are discussed. We offer valid scales for use in internal communication assessment. The book concludes with predictions of the future of internal communications research, theory development, and practices.-- Provided by Publisher
Keywords: Relaciones públicas; Cambio organizacional; Comunicación en la empresa